Expression of Galectin-3 in pancreatic ductal adenocarcinoma - Gaida, Matthias; Bach, Sylvia Tosca; Günther, Frank; Baseras, Billur; Tschaharganeh, Darjus-Felix; Welsch, Thilo; Felix, Klaus M.; Bergmann, Frank; Hänsch, Gertrud Maria; Wente, Moritz N. (Pathology & oncology research, 2012)
Galectin-3 influences neoangiogenesis, tumor cell adhesion, and tumor-immune-escape mechanisms. Hence, the expression of galectin-3 in pancreatic ductal adenocarcinoma (PDAC) was evaluated. Galectin-3 expression in PDAC cell lines was proven by the presence of intracellular protein and by release into the supernatant. Furthermore, galectin-3 was found in the majority of human tissue samples. Serum concentrations of galectin-3 in PDAC patients did not differ significantly from healthy donors and did not correlate with established tumor markers. In conclusion, galectin-3 is expressed in PDAC tissues suggesting a role in tumor development; however, no relationship between expression and clinical findings could be established.
First online: 12 September 2011
Gesehen am 08.06.2018